Crescimento e produção de batata-doce em função de doses de nitrogênio, espaçamentos e número de ramas por cova - Rosado, Anne Katherine de Holanda Bezerra (2016)
In the northeastern region, sweet potatoes have great social importance as a source of human nutrition, in addition to collaborating with the generation of employment and income, yet their productivity is still low when compared to the national average. In order to evaluate the growth and production of sweet potatoes as a function of nitrogen doses, spacings and number of branches per pit, a field experiment was set up at the Agricultural Sciences Center of the Federal University of Paraíba, Areia, PB, Brazil. The Regolítico, Psamítico. The experimental design was of randomized blocks in subdivided plots with four replications. In the plots, 15 treatments consisting of five nitrogen doses (0, 60, 120, 180 and 240 kg ha-1), combined with three plant spacings (0.30, 0.40 and 0.50 m), and in the subplots, different numbers of plants (one and two branches). Green and dry mass of shoot-1, SPAD index, leaf area, leaf area index, average commercial root mass, commercial root-plant yield, total and commercial rootstock yield, N, Leaf P and K and starch content of the roots. The total productivity reached a maximum of 49 t ha-1, at a spacing of 0.30 m with one branch per pit at the dose 168 kg ha-1, for commercial production its maximum value of 33.9 t ha-1 was reached With one branch limb and 144 kg ha-1 of nitrogen. All growth characteristics of sweet potato were altered by nitrogen fertilization, spacings between plants and number of branches per pit.